2013
DOI: 10.1074/jbc.m113.450536
|View full text |Cite
|
Sign up to set email alerts
|

LIM-homeodomain Transcription Factor Isl-1 Mediates the Effect of Leptin on Insulin Secretion in Mice

Abstract: Background: Leptin and Isl-1 have functions to regulate the insulin secretion, but the interaction between Leptin and Isl-1 remains unknown. Results: Isl-1 mediates the signaling pathway of leptin affecting insulin secretion. Conclusion: Isl-1 and STAT3 are the keynote proteins linking the leptin and insulin signaling networks. Significance: These findings are crucial for understanding the mechanisms of insulin secretion and metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(54 reference statements)
3
16
0
Order By: Relevance
“…In the pancreas, STAT3 signaling is required for the correct development and maintenance of endocrine pancreas (11). In addition, leptin-induced activation of STAT3 plays a crucial role in inhibiting insulin secretion in mice (12).…”
mentioning
confidence: 99%
“…In the pancreas, STAT3 signaling is required for the correct development and maintenance of endocrine pancreas (11). In addition, leptin-induced activation of STAT3 plays a crucial role in inhibiting insulin secretion in mice (12).…”
mentioning
confidence: 99%
“…Complex cell signalling pathways intimately regulate insulin expression in the pancreatic cells. Our recent studies suggest that Isl1 regulates the effect of leptin and kisspeptin on insulin secretion in mice2223, so we speculate that the interaction between PIASy and Isl1 may be involved in mediating insulin gene expression and secretion. Coinciding with the above thought, both PIASy and Isl1 are expressed in human and mouse pancreas and NIT beta cells.…”
Section: Discussionmentioning
confidence: 84%
“…In our recent studies, Isl1 was suggested to regulate the effect of leptin and kisspeptin on insulin secretion in mice2223. To identify whether the interaction between Isl1 and PIASy is involved in regulating insulin synthesis and secretion, first we detected the expressions of PIASy and Isl1 in mouse pancreatic islet and NIT beta cells using standard PCR and immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations